2019
DOI: 10.1152/ajpgi.00199.2019
|View full text |Cite
|
Sign up to set email alerts
|

Enteric neuron density correlates with clinical features of severe gut dysmotility

Abstract: Gastrointestinal (GI) symptoms can originate from severe dysmotility due to enteric neuropathies. Current methods used to demonstrate enteric neuropathies are based mainly on classic qualitative histopathological/immunohistochemical evaluation. This study was designed to identify an objective morphometric method for paraffin-embedded tissue samples to quantify the interganglionic distance between neighboring myenteric ganglia immunoreactive for neuron-specific enolase, as well as the number of myenteric and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The mortality in CIPO is often attributed to the intestinal failure and leakiness of the gut owing to the abnormalities of intestinal epithelial and vascular barrier. 17 One of our cases succumbed to the illness due to septicemia and we believe a similar etiopathogenesis in the index case.…”
Section: Discussionsupporting
confidence: 54%
“…The mortality in CIPO is often attributed to the intestinal failure and leakiness of the gut owing to the abnormalities of intestinal epithelial and vascular barrier. 17 One of our cases succumbed to the illness due to septicemia and we believe a similar etiopathogenesis in the index case.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, CIPO has been reported in patients with autosomal dominant mutations in the SOX10 gene in Waardenburg-Shah syndrome [ 90 ], and is also related to sex chromosome inheritance in Xq28 with mutations in Filamin A and L1CAM genes [ 91 , 92 ]. Although abnormalities in gastrointestinal motility in patients with CIPO manifest in the presence of enteric ganglia [ 85 ], a neuronal deficit of approximately 50% associated with increased distance between ganglia, neuronal swelling and axonal degeneration and which correlates with the degree of symptom severity has been reported [ 93 ]. This is also the case for slow transit constipation, defined by reduced and infrequent intestinal transit, sensation of anorectal obstruction and solid fecal content [ 94 ].…”
Section: Enteric Neuropathiesmentioning
confidence: 99%
“…In a recent study, jejunal full-thickness biopsies were collected from patients suffering from severe gut dysmotility, either by laparoscopy or by conventional abdominal laparotomy. By quantifying the inter-ganglionic distance between neighboring myenteric ganglia and the number of neurons per ganglion in the myenteric and submucosal plexus, the authors showed that patients with enteric dysmotility had significantly fewer myenteric and submucosal neurons [ 140 ]. The methodology has been refined, and a new technique has utilized the evaluation of standard submucosal biopsies.…”
Section: Emerging Methods For Assessment Of Gastroenteropathymentioning
confidence: 99%